Aplicação de técnicas analíticas na investigação e controle do processo de torrefação de cafés - Debona, Danieli Grancieri (2023)
The quality of the coffee production chain is achieved through the monitoring of its production stages, with roasting being a prominent step. The roasting process is governed by the time-temperature relationship to which coffee beans are exposed, resulting in the roast profile that is categorized into stages: dehydration, roasting (yellow, cinnamon, crack, and development), and burning (post-roasting). Defining these stages is a complex undertaking, given the limited knowledge about the chemical alterations occurring in each, necessitating the utilization of sensory parameters to delineate their subdivisions. In this context, the utilization of analytical techniques and physicochemical parameters becomes pivotal tools for comprehending the recurring chemical changes within the beans during roasting. Moreover, when employed synergistically with sensory analysis, they augment the understanding of the interplay between the chemical composition of the beans and the sensory attributes of the beverage, thereby enabling the identification of chemical markers that best characterize the roast stages. In light of this, the primary objective of this study is to investigate the chemical and sensory alterations occurring in coffees of the Coffea canephora and Coffea arabica species throughout the course of the roasting process. This objective encompasses the determination of the optimal roasting point and the characterization of its stages, with a focus on correlating sensory attributes and descriptors with the chemical composition of the coffee. To this end, samples were collected minute by minute in a roasting profile. Sensory analyses (by SCA and UCDA), physicochemical assays (including pH, water activity, soluble solids, colorimetry, and titratable acidity), mid-infrared spectroscopic analysis, and gas chromatography coupled with mass spectrometry were conducted. Chemometric tools were employed to assess the potential of utilizing analytical techniques and sensory analysis in the observation of grain transformations during roasting. As a result, it was observed that for both coffee types, sensory analysis yields higher evaluations for the minutes corresponding to the development roast stage, and the utilized descriptors exhibit similarities for the minutes in accordance with the roast stages. In the realm of physicochemical analyses, pH, titratable acidity, water activity, colorimetry, and soluble solids are capable of distinguishing the coffee based on the roast stage. Bands at 3500- 3000 cm-1, 2920-2855 cm-1, 1750-1700 cm-1, and 1200-900 cm-1 within the infrared spectrum emerged as the most informative for developing calibration models capable of predicting the roast stages. The results from gas chromatography were also able to discriminate the samples in accordance with these stages. The volatile compound classes exhibited positive correlations between pyrroles and furanones, as well as negative correlations between alcohols and ketones. Aldehydes, anhydrides, ketones, and furans were found to exert a significant impact on the sensory quality of the samples, in contrast to alcohols and xanthines, which were negatively correlated with quality.